How who you know impacts on what you know : A qualitative study into the partnership and employment strategies of South African companies in Sub-Saharan Africa, using social network theory - Rowley, Colin (University of Pretoria, 2016)
Mini Dissertation (MBA)--University of Pretoria, 2015.